Advances in active suspension systems for road vehicles - Yu,M; Evangelou,S; Dini,D (Engineering, 2024)
Active suspension systems (ASSs) have been proposed and developed for a few decades, and nowadays again become a thriving topic in both academia and industry, due to the high demand in driving comfort and safety, and the compatibility with vehicle electrification and autonomy. Existing review papers on ASSs are mainly about dynamics modelling and robust control, however, the gap between academic research outcomes and industrial application requirements is not yet bridged, hindering most ASS research knowledge from transferring to vehicle companies. This paper comprehensively reviews advances in ASSs for road vehicles, focusing on hardware structures and control strategies. Particularly, state-of-the-art ASSs that have been recently adopted in production cars are detailed, including representative solutions of Mercedes Active Body Control and Audi Predictive Active Suspension; novel concepts that could become alternative candidates are also introduced, including the Series Active Variable Geometry Suspension, and the Active Wheel Alignment System. The ASSs with compact structure, small mass increment, low power consumption, high frequency response, acceptable economic costs and high reliability are more likely to be adopted by car manufacturers. In terms of control strategies, future ASSs not only aim to stabilize the chassis attitude and attenuate the chassis vibration, moreover, but also cooperate with other bodies (e.g., steering and braking) and sensors (e.g., camera) within a car, and even with high-level decision (e.g., reference driving speed) in the overall transportation system – these strategies will be compatible with the rapidly developed electric and autonomous vehicles.